Eclipse - Meyer, Stephenie 1973- (2007)
Bella must choose between her friendship with Jacob, a werewolf, and her relationship with Edward, a vampire, but when Seattle is ravaged by a mysterious string of killings, the three of them need to decide whether their personal lives are more important than the well-being of an entire city.
Ultimatum -- Evasion -- Motives -- Nature -- Imprint -- Switzerland -- Unhappy ending -- Temper -- Target -- Scent -- Legends -- Time -- Newborn -- Declaration -- Wager -- Epoch -- Alliance -- Instruction -- Selfish -- Compromise -- Trails -- Fire and ice -- Monster -- Snap decision -- Mirror -- Ethics -- Needs -- Epilogue : Choice.
Prequel: New moon.
Sequel: Breaking dawn.
Keywords: Swan, Bella (Fictitious character) -- Juvenile fiction; Cullen, Edward (Fictitious character) -- Juvenile fiction; Vampires -- Juvenile fiction; Werewolves -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Triangles (Interpersonal relations) -- Juvenile fiction; Young adult fiction; Seattle (Wash.) -- Juvenile fiction; Washington (State) -- Juvenile fiction